THU0010 THE ANTI-INFLAMMATORY CYTOKINE INTERLEUKIN 37 IS AN ENDOGENOUS INHIBITOR OF TRAINED IMMUNITY. (June 2019) - Cavalli, Giulio; Gresnict, Mark; Arts, Rob; Nemkov, Travis; D'alessandro, Angelo; Giugliano, Silvia; Eisenmesser, Elan; Dagna, Lorenzo; Joosten, Leo; Netea, Mihai; Dinarello, Charles
Abstract : Background: Trained immunity (TI) is a de-facto innate immune memory program induced in monocytes/macrophages by exposure to pathogens or vaccines, which evolved as a protective mechanism against infections. TI is characterized by rewiring of functional, epigenetic and metabolic programs of innate immune cells such as monocytes and macrophages, which sustain enhanced production of pro-inflammatory cytokines. Since aberrant activation of TI is implicated in inflammatory diseases, tight regulatory mechanisms are likely in place, but the mechanisms responsible for this modulation remain elusive. Objectives: Scope of this study was to evaluated the role of IL-37, an anti-inflammatory cytokine that curbs inflammation as well as modulates metabolic pathways, as an endogenous regulator of trained immunity. Methods: The effects of recombinant IL-37 were evaluated in a mouse model of TI induced by the administration of beta-glucan in vivo (survival to a lethal inoculum of infectious agents, production of inflammatory cytokines, recruitment of inflammatory cells at the sites of infection). Subsequently, the effects of IL-37 were evaluated ex vivo on bone marrow monocytes (production of inflammatory cytokines, metabolomic analysis of the activation status of the main pathways of cellular energy metabolism). Finally, we evaluated the association between IL-37 gene polymorphisms and the induction of TI in monocytes of healthy donors with in vitro functional studies. Results: The exogenous administration of IL-37 abrogated the pro-inflammatory effects of TI, significantly reducing the production of pro-inflammatory cytokines and the survival of experimental animals subjected to a model of disseminated infection. The inhibitory effects of IL-37 on TI were also associated with reduced recruitment of neutrophils at sites of inflammation. IL-37 and TI programs had differential and opposite effects on the modulation of cellular energy metabolism of monocytes. In humans, polymorphisms in the IL-37 gene were associated with reduced activation of TI programs and reduced production of inflammatory cytokines by healthy donor monocytes. Conclusion: In conclusion, IL-37 emerges as an endogenous regulator of TI, which makes this cytokine a potential therapeutic target in immune-mediated pathologies. References: [1] M. G. Netea, et al., Trained immunity: A program of innate immune memory in health and disease. Science. (2016). [2] G. Cavalli, C. A. Dinarello, Suppression of inflammation and acquired immunity by IL-37. Immunol Rev (2018). Disclosure of Interests: None declared